The truth about teaching : an evidence-informed guide for new teachers - Ashman, Greg (Sage, 2018)
Drawing on years of experience teaching in a diverse range of schools and powered by a nuanced understanding of educational research, Greg Ashman presents the most vital ideas that you need to know in order to succeed in teaching. Find out how to avoid common mistakes and challenge some of the myths about what good teaching really is. Evidence-informed, the book explores major issues you will encounter in schools, including the science of learning, classroom management, explicit forms of teaching, why the use of phonics has been such a controversial issue and smart ways to evaluate the potential of technology in the classroom.